Stain differentiation of South African clinical isolates of Mycobacterium tuberculosis by restriction and amplified fragment length polymorphisms - Nel, Louis Hendrik (University of Pretoria, 2013)
Dissertation (MSc(Microbiology))--University of Pretoria, 2006.